Customer Satisfaction in Private Pharmacies in Al-Bayda City: The Role of Pharmaceutical Care Service Quality - Hanadi Amhimmid (AlQalam Journal of Medical and Applied Sciences, 2025)
This research examines the quality of pharmaceutical care services offered by private pharmacies in Al-Bayda city, focusing on key service quality aspects and their effect on customer satisfaction. Using a descriptive-analytical approach, the study employed a structured questionnaire administered to 200 pharmacy customers. Data analysis involved calculating means and standard deviations, while multiple linear regression (conducted via SPSS) was used to test hypotheses. Results showed that service providers exhibit strong competence in delivering quality care, with an overall mean score of 3.97, suggesting high respondent agreement. Customer satisfaction was moderately high, averaging 3.79. Regression analysis confirmed a significant link between service quality dimensions and satisfaction, with Reliability and Tangibility having the strongest positive influence. The study suggests that improving these specific dimensions could enhance customer satisfaction in Al-Bayda’s private pharmacies.